ESTUDO DA SAZONALIDADE DE ALPHITOBIUS DIAPERINUS EM CRIAÇÃO DE GALINHAS POEDEIRAS POR TRÊS DIFERENTES MÉTODOS DE COLETA - Lopes, W.d.z. [UNESP]; Costa, F.h. Da; Lopes, W.c.z.; Soares, V.e. [UNESP]; Balieiro, J.c. De C.; Prado, Â.p. Do (Instituto Biológico, 2022)
Alphitobius diaperinus, considered a secondary plague of stored grains, is commonly found in industrial aviaries excrements in some parts of the world. It causes economic damages in poultry houses in such a waydirectly, as well as indirectly. A survey of this tenebrionidae in a commercial grange situated in São João da Boa Vista city was carried out from January 2001 to December 2002, by using three distinct collect methods: soil trap, funnel of Berlese-Tullgren and fluctuation in water. Of the total of insects, 94.19% were collected by soil trap, 1.78% by funnel of Berlese-Tullgren and 4.01% by fluctuation in water. This coleopteran was found in all the 75 collectscarried out during the 24 months of experiment, and the soil trap the most sensible method (P < 0.05) for the capture of A. diaperinus.

Alphitobius diaperinus(Panzer, 1979), considerado uma praga secundária de grãos armazenados, é comumente encontrado com abundância nos substratos de aviários industriais em várias partes do mundo, causando prejuízos econômicos tanto direta quanto indiretamente. Foi realizado um levantamento deste tenebrionídeo em uma granja comercial de galinhas poedeiras situada no Município de São João da Boa Vista, SP, entre janeiro de 2001 a dezembro de 2002, utilizando-se três métodos distintos de coleta: armadilhas de solo, funil de Berlese-Tullgren e flutuação em água. Do total de insetos coletados, armadilhas de solo somaram 94,19% de toda população, 1,78% pelo funil de Berlese-Tullgren e 4,01% de cascudinhos capturados pela flutuação em água. Esta espécie de coleóptero ocorreu nas 75 coletas realizadas nos 24 meses de experimento, sendo as armadilhas de solo o método mais sensível (P < 0,05) para captura de A. diaperinus.
STUDY OF THE SAZONALITY OF ALPHITOBIUS DIAPERINUS IN CREATION OF LAYER HOUSE FOR THREE DIFFERENT METHODS OF COLLECTION
Keywords: Layer house; lagged layer manure; Tenebrionidae; animal production; Aves poedeiras; esterco de aves poedeiras; produção animal; Tenebrionidae